An improved method for the purification of tRNA by chromatography on dihydroxyboryl substituted cellulose. - McCutchan, T F (1975)
An improved method for the rapid separation of aminoacyl-tRNA from tRNA by chromatography on dihydroxyboryl-substituted cellulose has been developed. The method relies on the selective binding of unacylated tRNA to the cell cellulose support containing dihydroxyboryl groups. This binding is the result of complex formation between the cis-diol group of the 3'-terminal ribose in tRNA and the dihydroxyboryl groups immobilized on the resin. Aminoacyl-tRNA cannot undergo borate complex formation and is not retained on the resin. The separation is carried out at near neutral pH values ensuring stability of the aminoacyl ester linkage. The aminoacyl-tRNAs are obtained in very high purity. Aminoacyl-tRNA species containing the modified nucleoside Q are also retained on dihydroxyboryl cellulose. Conditions for isolating all Q base containing tRNA species from unfractionated tRNA are described.